A randomized direct comparison of the pharmacokinetics and pharmacodynamics of apixaban and rivaroxaban [Corrigendum] - Frost C; Song Y; Barrett YC; Wang J; Pursley J; Boyd RA; LaCreta F (Dove Medical Press, 2018)
Frost C, Song Y, Barrett YC, et al. Clin Pharmacol. 2014;6:179–187.Page 183, Figure 2, the arithmetic mean apixaban trough concentration on Day 4 prior to the morning dose (ie, 0-hr Figure 2) was not correct. The arithmetic mean (SD) apixaban trough concentration on Day 4 prior to the morning dose was 24.6 (6.1) ng/mL. Read the original article.